COVID-19 pandemic-imposed lockdown: impacts on the rural agrarian and the urban corporate workforce of India. Issue 11 (2nd November 2022) - Majumdar, Piya; Mandi, Sasangbaha; Biswas, Ankita; Nayak, Prasunpriya; Sahu, Subhashis
ABSTRACT: The impact of the COVID-19 pandemic is inescapable which encompasses both physical and mental health myriads. To combat the pandemic, lockdown has been imposed worldwide, the impact of which, and, the subsequent new normal phase has raised global concern. Two workforces of the Indian population, rural agrarian and urban corporate, were compared for impact on sleep quality, depressive symptomatology, screen exposure, somatic pain and other health co-morbidities in three-time frames – prior, during and post lockdown periods. An online survey was conducted for those engaged in the urban corporate sector (N=146) and an interview for the rural agrarian workforce (N=100). Both the workforces had adumbrated significant (p<0.05) variations in sleep behavior with changes noted in sleep latency and feeling of sleepiness, being higher during the lockdown phase. The screen time had also been identified to be positively related to the presence of depressive symptomatology and negatively with sleep duration among both the workforces. Our findings suggest that COVID-19 induced lockdown affects the urban corporate more with erratic sleep behavior, enhanced psychometric distress, somatic discomfort and behavioral modifications that might be due to social isolation, reliance over digital use, and disoriented work schedule     .